2015
DOI: 10.1002/lary.25655
|View full text |Cite
|
Sign up to set email alerts
|

Facial nerve stimulation in the narrow bony cochlear nerve canal after cochlear implantation

Abstract: 4. Laryngoscope, 126:1433-1439, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
0
10
0
4
Order By: Relevance
“…Studies with data exclusively on pediatric patients reported FNS rates ranging from 1.1% to 7.1% (Table 1). 4,[8][9][10][11][12] Reports of FNS are primarily based on subjective descriptions by the patient or visual detection of facial movements, which may partially explain lower rates of FNS among pediatric patients. Children are often unable to adequately identify their symptoms, causing oversight of this complication in the pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…Studies with data exclusively on pediatric patients reported FNS rates ranging from 1.1% to 7.1% (Table 1). 4,[8][9][10][11][12] Reports of FNS are primarily based on subjective descriptions by the patient or visual detection of facial movements, which may partially explain lower rates of FNS among pediatric patients. Children are often unable to adequately identify their symptoms, causing oversight of this complication in the pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 These complications are generally associated with close neighboring of these structures or a narrow bony cochlear nerve canal. 5…”
mentioning
confidence: 99%
“…Early and late complications of CI are well known. Complications related to the facial nerve, including facial nerve palsy and stimulation, occur relatively less than do vestibular and cochlear complications 4,5 . These complications are generally associated with close neighboring of these structures or a narrow bony cochlear nerve canal 5 …”
mentioning
confidence: 99%
See 2 more Smart Citations